Suspected Metallic Embolization Distal to Coiled Intracranial Aneurysms Detectable by Susceptibility-Weighted MR Imaging - Yoo, D.H.; Cho, Y.D.; Lee, H.S.; Kim, S.H.; Jang, D.; Lee, S.H.; Cho, W.-S.; Kang, H.-S.; Kim, J.E.; Han, M.H. (American Journal of Neuroradiology, 2020)
BACKGROUND AND PURPOSE: After endovascular coiling of intracranial aneurysms, round dark parenchymal lesions believed to be particulate metal are sometimes encountered in MR imaging studies of the brain. We used SWI to assess the frequency of such occurrences, in addition to exploring likely causes and clinical implications.MATERIALS AND METHODS: We reviewed 700 MR imaging studies performed between September 2018 and March 2019 at our institution as follow-up monitoring of coiled intracranial aneurysms. Any sizeable (>5 mm) rounded dark-signal lesions encountered were presumed to be metallic. The magnitudes and locations of such lesions were recorded. In patients with these lesions, pertinent procedural documentation was screened for devices used, including coils, microcatheters, microguidewires, and stents. Medical records were also examined to determine whether any related symptoms ensued.RESULTS: Twenty patients (2.8%) exhibited a total of 25 lesions on SWI. Diameters ranged from 5 to 11 mm (median, 8 mm). All except 2 lesions were located in brain regions downstream from aneurysms, but all lesions occupied vascular territories of vessels used to place guiding catheters. Other than the Synchro 14, which was routinely deployed, no device was regularly used in patients with SWI-detectable lesions; and none of the affected patients developed focal neurologic symptoms as a consequence.CONCLUSIONS: Although the origins remain unclear, distal embolization of particulate metal distal to coiled cerebral aneurysms is occasionally observed on follow-up MR imaging studies. Such lesions, however, seem to have no apparent clinical impact.AcomAanterior communicating arteryICAinternal carotid arteryMCAmiddle cerebral artery